Soft tissue free flap for reconstruction of upper extremities: a meta-analysis on outcome and safety - Zhang, Ying; Gazyakan, Emre; Bigdeli, Amir Khosrow; Will-Marks, Patrick; Kneser, Ulrich; Hirche, Christoph (Microsurgery, 2019)
Background The aim of this study was to evaluate outcome and safety of free flaps to the upper extremity by pooled, summarized rates, compared with the existing pooled results of the lower extremity from literature, and to improve the level of evidence in a meta-analysis. Methods A literature search of PubMed and Embase was conducted addressing publications between January 2000 and April 2018. Publications were selected by inclusion/exclusion criteria on safety and outcome. Postoperative complications were statistically analyzed: flap loss, vessel thrombosis; recipient-site infection, hematoma, seroma, wound dehiscence, dysesthesia; donor-site morbidity. Results Two hundred and seventy-nine patients with 283 free flaps from 23 publications were extracted and eligible for this meta-analysis. The predominant donor site was the lower extremity (56%), with the anterolateral thigh flap as the major workhorse (30%). The summarized rate of total and partial flap loss was 6.0% (95% CI = 3.0-9.0%, PQ = 1.0000) and 8.0% (95% CI = 6.0-13.0%, PQ = 0.9973), respectively. The rate of arterial and venous thrombosis was 5.0% (95% CI = 3.0-9.0%, PQ = 0.9999) and 8.0% (95% CI = 9.0-37.0%, PQ = 0.9804), respectively. Complication rates of recipient site were: early infection with 7.0% (95% CI = 4.0-11.0%, PQ = 0.9788), hematoma with 6.0% (95% CI = 3.0-8.0%, PQ = 1.0000), seroma with 6.0% (95% CI = 4.0-10.0%, PQ = 0.9948), dehiscence with 7.0% (95% CI = 4.0-11.0%, PQ = 0.9988), and dysesthesia with 6% (95% CI = 4.0-10.0%, PQ = 0.9988). The rate of donor-site morbidity was 14% (95% CI = 8.0-21.0%, PQ = 0.0895). Conclusions Soft tissue free flaps to the upper extremity have comparable success rates, but higher perioperative complication rates (e.g., partial flap loss, infection, and wound dehiscence) compared to the pooled data of lower extremity reconstruction from existing meta-analysis.
Gesehen am 29.01.2021